Lignocellulosic byproducts as filler in polypropylene: Comprehensive study on the effects of compatibilization and loading. Issue 2 (27th April 2012) - Fuqua, Michael A.; Chevali, Venkata S.; Ulven, Chad A.
Abstract Lignocellulosic byproducts derived from biofuel processes were analyzed as functional fillers in polypropylene‐based biocomposites. Corn cob, a byproduct yielded from corn harvesting for ethanol production, and sunflower hull, a byproduct of seed stripping for biodiesel production, were both examined as ground filler agents. Composite blends with these lignocellulosic fillers at four filler loadings and four variants of surface compatibilizer loading were melt‐compounded using a twin screw extruder and injection molded into test specimens. Tensile testing, notched Izod impact testing, and thermal‐mechanical analysis were performed on the composites. The role of filler type, loading, and surface compatibilization were established and reported. Additionally, elastic modulus and tensile strength were successfully modeled using established particulate composite models. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013